Analytical evaluation of fining treatments for white wines contaminated by Ochratoxin A - Carvalho, Filipa (2014)
Mycotoxins are toxic secondary metabolites produced by certain molds. Ochratoxin A (OTA) is one of the most relevant. Its chemical structure is a dihydro-isocoumarin connected at the 7-carboxy group to a molecule of L--phenylalanine via an amide bond. OTA in wine is a risk to consumer health [1]. According to the Regulation No. 123/2005 of the European Commission, the maximum limit for OTA in wine is 2 µg/kg [2]. Then, it is important to control its occurrence. So, the aim of this work was to know the effect of different fining agents on OTA removal from white wine.